Redescription of Echinoderes levanderi Karling, 1954 (Kinorhyncha: Cyclorhagida) – a kinorhynch tolerant to very low salinities - Sørensen, Martin V. (European Journal of Taxonomy, 2018)
The kinorhynch species Echinoderes levanderi Karling, 1954 is redescribed. The species can now be recognized by the presence of spines in middorsal positions on segments 4–8, and in lateroventral positions on segments 6–9, with lateroventral spines on segment 9 showing sexual dimorphism; tubes in subdorsal and ventrolateral positions on segment 2, in sublateral positions on segments 4 and 8, in lateroventral positions on segment 5, and in laterodorsal positions on segment 10. Furthermore, the enlarged sieve plates on segment 9 make the species highly characteristic. New records of the species extend its distributional range into the Bothnian Bay where the bottom water salinity drops below 5 ppt, which is the lowest salinity recorded for a habitat with kinorhynchs.